The power in the interview: A practical guide for identifying the critical role of actor interests in environment research - Ahmad Maryudi; Micah R. Fisher (Forestry Faculty, Universitas Hasanuddin, 2020)
In policy discussions of sensitive and complex issues, particularly in the field of forestry and natural resources, interests play an integral role, but are often a challenging component to contextualize, understand, and study. For various reasons related to factors of influence and authority, actors often do not want their interests uncovered by either competitors or even by non-partisan researchers. Nevertheless, identifying such interests continue to be a critical task for the research community, particularly if we are to better understand the broader effects, effectiveness, or shortcomings of policy. In this short policy brief, we provide a practical guide for researchers to capture and incorporate actor interests as part of their empirical evidence through the interview process. Following an empirical-analytical approach, we first distinguish interests of two different types, the formal and informal. Thereafter, our guide lays out an approach consisting of four distinct phases, namely: i) deciding on the interview format, ii) creating situational settings for the interview, iii) preparing interview guides; and iv) triangulating the interview. In each phase, we underline the importance of a culture of generosity and positivity directed toward the interviewees, comfortably engaging them to describe factors and scenarios in rich detail, while also encouraging respondents to express their values and feelings toward both the area of study and other actors across policy networks.Actor interests are always a sensitive issue in policies related to the environment, which are often purposefully hidden by actors, and commonly overlooked by research;We develop a practical guide based on a set of principles for researchers to use when approaching interviews, which will help to more effectively understand and contextualize actor interests, and can ensure more robust findings about policies related to the environment and natural resources;This guide lays out four distinct phases for approaching the complex and sensitive issue of actor interests for data collection using interviews, namely through the way researchers i) structure interview formats, ii) set up situational settings, iii) approach the preparation and delivery of guiding questions, and iv) triangulate the interview.